A study to understand the health seeking behaviour pattern and healthcare utilisation of peri-urban people in Vadodara district, Gujarat - Rucha Dave; Piyushkumar C. Parmar; Pooja Singh; Maulik Desai; Niraj Pandit (Journal of Family Medicine and Primary Care)
Background: The definition of delivering healthcare services is “the timely use of personal health services to achieve the best possible health outcomes”. Due to social, economic and health policy considerations, different countries, groups and individuals may have varying degrees of access to healthcare. Limitations on healthcare services have a negative influence on treatment effectiveness, consumption of medical services. The objective of this study is to understand the pattern of healthcare-seeking behaviour in adults and also their healthcare services utilisation. Methodology: A cross-sectional community-based study in peri-urban population of Vadodara, Gujarat, was done for a period of 3 months. Results: 51% participants were male, and 48% participants were female. Most the participants belonged to Class 1 and 2 socio-economic class. The factors such as socio-economic status, visitation and awareness about full body checkup, travelling and cost-related variables were found to be statistically significant. The awareness and health-seeking nature was seen more in the younger (40-59) population than the older population, mainly because of the distance. However, doctors’ advice was more followed through by the elderly population. Conclusion: Financial limitations, distance and transportation costs, the ability to take paid time off work to use services, personal constraints and poor health literacy are some of the factors to consider when it comes to healthcare access.